Bounded index, entire solutions of ordinary differential equations and summability methods - G. H. Fricke; Ranjan Roy; S. M. Shah (International Journal of Mathematics and Mathematical Sciences)
A brief survey of recent results on functions of bounded index and bounded index summability methods is given. Theorems on entire solutions of ordinary differential equations with polynomial coefficients are included.